Structure and mechanical properties of multilayer coatings (TiAlCrY)N/ZrN - Novikov, V.Yu.; Beresnev, V.М.; Kolesnikov, D.A.; Ivanov, О.N.; Lytovchenko, S.V.; Stolbovoy, V.A.; Kolodiy, I.V.; Kozachenko, A.O.; Kovaleva, M.G.; Kritsyna, E.V.; Glukhov, О.V. (Вопросы атомной науки и техники, 2019)
Multiperiodic nitride coatings (TiAlCrY)N/ZrN with different layer thicknesses are formed by vacuum-arc evaporation in a nitrogen atmosphere (0.2…0.6 Pa) of two targets, TiAlCrY and Zr. The targets were located along one straight line at equal distances from the perpendicular axis on which the substrates were placed. The rotation of the axis with the substrates was carried out either continuously or with a fixed delay at the evaporators. The duration of the process was chosen so that the total thickness of the coating (total thickness of the bilayers) was 10…11 μm. The effect of nitrogen pressure and modulation period on the structural-phase state, elemental composition, and mechanical properties of multilayer coatings has been studied. An increase in the partial pressure of nitrogen and, consequently, its content in the coating leads to an increase in hardness. Reducing the thickness of the layers in the coatings increases the adhesive strength of the coatings and does not have a significant effect on the microstresses in the coating. Багатоперіодичні нітридні покриття (TiAlCrY)N/ZrN з різною товщиною прошарків сформовані вакуумно-дуговим випаровуванням в азоті (0,2…0,6 Па) двох мішеней – TiAlCrY і Zr. Мішені розташовували на одній прямій на рівних відстанях від перпендикулярної осі, на якій кріпилися підкладинки. Обертання осі з підкладинками здійснювали або безперервно, або з фіксованою затримкою у випарників. Тривалість процесу вибирали так, щоб загальна товщина покриття (сумарна товщина подвійних прошарків) становила 10…11 мкм. Проаналізовано вплив тиску азоту і періоду модуляції на структурнофазовий стан, елементний склад і механічні властивості багатошарових покриттів. Збільшення парціального тиску азоту і внаслідок цього  його вмісту в покритті призводить до збільшення твердості. Зменшення товщини шарів у покриттях збільшує адгезійну міцність покриттів та істотно не впливає на мікронапруження в покритті. Многопериодичные нитридные покрытия (TiAlCrY)N/ZrN с различной толщиной слоев сформированы вакуумно-дуговым испарением в среде азота (0,2…0,6 Па) двух мишеней – TiAlCrY и Zr. Мишени располагали вдоль одной прямой на равных расстояниях от перпендикулярной оси, на которой располагали подложки. Вращение оси с подложками осуществляли либо непрерывно, либо с фиксированной задержкой у испарителей. Длительность процесса выбирали так, чтобы общая толщина покрытия (суммарная толщина бислоев) составляла 10…11 мкм. Проанализировано влияние давления азота и периода модуляции на структурно-фазовое состояние, элементный состав и механические свойства многослойных покрытий. Увеличение парциального давления азота и вследствие этого – его содержания в покрытии приводит к увеличению твердости. Уменьшение толщины слоев в покрытиях увеличивает адгезионную прочность покрытий и не оказывает существенного влияния на микронапряжения в покрытии.